The Labor Market in Poland and the Social Responsibility of the State and Business: Comparative Aspects - Anna Krajewska; Stefan Krajewski (Comparative Economic Research. Central and Eastern Europe, 2020)
Since the beginning ofthe transformation ofthe Polish economy, Many disturbing phenomena have appeared onthe labour market inPoland. This paper points out toseveral ofthem, namely: 1) inconsistency inrespecting the rules ofthe market mechanism and the important role ofpolitical decisions, 2) long-term persistence ofhigh unemployment rate and low effectiveness ofmethods ofcombating unem-ployment, 3) low wages and rising income diversification, 4) high share ofnon-stand-ard forms ofemployment intotal employment. The scale ofthese disturbing phenom-ena isbigger than inother economies under transformation.Inresponse tothe imperfections ofthe market, many publications concerning cor-porate social responsibility appeared inPoland. According tothe authors the reasons for the shortcomings ofthe labour market discussed inthe paper should, however, besought not only inthe non-respect ofthe principles ofcorporate social responsi-bility, but also inthe weaknesses ofthe adopted systemic solutions and weaknesses ofinstitutions ofthe State.
Keywords: J01; J08; P20; 330; labour market; transition ofthe economy; Corporate Social Responsibility